Pemenuhan Hak Restitusi Bagi Korban Tindak Pidana Perdagangan Orang - Ramadhan, Shendy; Widiarto, Bambang; Sudarto, Sudarto (FOCUS, 2025)
Human trafficking violates human rights as it involves threats, coercion, deception, and abuse of power for exploitative purposes such as prostitution, forced labor, and slavery. Victims of this crime are entitled to restitution as compensation provided by the offender or a third party. This study applies a normative juridical method to examine the regulation and implementation of victims' restitution rights based on Articles 48–51 of Law No. 21/2007, Article 7A of Law No. 31/2014, Government Regulation No. 43/2017, and Prosecutorial Guidelines No. 1/2021. The findings reveal that the implementation of restitution in Indonesia remains ineffective due to weak coordination among law enforcement agencies and limited understanding regarding proof of victims’ material and immaterial losses. Therefore, a specific legal framework is urgently needed to regulate the technical procedures for providing restitution, ensuring that victims of human trafficking receive their rightful compensation effectively, fairly, and in accordance with justice principles.